Semen analysis revisited- Qualitative assessment of sperms using cytochemical stains- the new norms of male infertility workup - Vidya K; Vishnupriya V; Radha R.K; Prathima S (Journal of Pathology of Nepal)
Background: Male infertility is on the rise globally. It contributes to about 40-50% of all infertility cases. Semen analysis forms the basic investigation for the assessment of male factors of infertility, but it has its pitfalls. Literature review has suggested newer parameters of semen analysis such as sperm quality, which can have a significant role in the outcome of pregnancy. This study aims to assess sperm DNA integrity and calculate the DNA fragmentation index, which is a measure of the quality of sperm, thereby highlighting the need for assessment of sperm quality along with sperm quantity.